# Monotony of the functionVerify the monotony of the function y=x^3-x^2+x+e^x.

### 1 Answer | Add Yours

You need to use monotonicity theorem, hence, you need to find derivative of the function, such that:

`f'(x) = 3x^2 - 2x + 1 + e^x`

You need to find the second order derivative of the function, such that:

`f''(x) = 6x - 2 + e^x`

You need to find the third order derivative of the function, such that:

`f'''(x) = 6 + e^x`

Since `f'''(x) > 0` for all x in R, hence, `f''(x),f'(x) > 0.`

**Hence, testing the monotony of the function, yields that `f(x) = x^3-x^2+x+e^x` increases if `x in R` .**